Optic Neuritis in the Older Chinese Population: A 5-Year Follow-Up Study. (11th December 2017) - Wang, Junqing; Zhou, Huanfen; Qin, Limin; Peng, Chunxia; Zhao, Jie; Teng, Da; Lin, Dahe; Ai, Nanping; Xu, Quangang; Wei, Shihui
Abstract : Objective . This study aims to describe the clinical manifestations and outcomes in a cohort of older Chinese patients. Method . A retrospective study of patients aged ≥ 45 years who had a first episode of optic neuritis (ON) between May 2008 and November 2012. Clinical features at onset and last follow-up were analyzed within subgroups (age 45–65 years and age ≥ 65 years). Results . 76 patients (99 eyes) were included, of which 58% were females. The mean age at presentation was 55.53 ± 8.29 years (range: 45–83 years). Vision loss was severe at presentation, with initial best corrected vision activity (BCVA) < 20/200 in 93% and final BCVA < 20/200 in 53% of patients at 5-year follow-up. Final BCVA significantly correlated with the initial BCVA and peripapillary retinal nerve fiber layer. At last follow-up, 14.5% were diagnosed with neuromyelitis optica spectrum disorder (NMOSD), 1.3% were diagnosed with multiple sclerosis (MS), 5.2% with chronic relapsing inflammatory optic neuropathy, 1.3% with infectious ON, and 19.7% with autoimmune ON. None of the elderly group (≥65 years) developed NMOSD or MS. Conclusion . Chinese patients in the age group ≥ 65 years with ON are less likely to develop NMOSD or MS. Notwithstanding, they had more severe visual loss at onset and poor recovery.